1998
DOI: 10.1016/s0014-5793(98)00220-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide‐caused fragmentation of individual microtubules in vitro observed by video‐enhanced differential interference contrast microscopy

Abstract: Microtubule disassembly is commonly believed to be a process of endwise tubulin dimer release. The present study demonstrates by video interference contrast microscopy that Escherichia coli lipopolysaccharide (LPS) caused microtubule disassembly in vitro by both endwise shortening and fragmentation. In contrast, the microtubules were only shortened from their ends in the presence of DNA, used as another example of a macromolecular microtubule effector. LPS-caused microtubule fragmentation was confirmed by tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…With biochemical and electron microscopy analyses, it has been shown that LPS can bind to microtubules and inhibit the polymerization of microtubules in vitro in a LPS concentration-dependent process (35). At lower concentrations, LPS selectively displaced the microtubule-associated proteins from the polymerized microtubules, whereas at higher concentrations, LPS inhibited the polymerization of microtubules (5). In the present study, LPS exposure reduced microtubule polymerization rapidly, within 1 min (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…With biochemical and electron microscopy analyses, it has been shown that LPS can bind to microtubules and inhibit the polymerization of microtubules in vitro in a LPS concentration-dependent process (35). At lower concentrations, LPS selectively displaced the microtubule-associated proteins from the polymerized microtubules, whereas at higher concentrations, LPS inhibited the polymerization of microtubules (5). In the present study, LPS exposure reduced microtubule polymerization rapidly, within 1 min (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…LPS targeted to intracellular microtubule architecture results in microtubule disassembly [32]. LPS can also bind to tubulin to cause microtubule fragmentation and shortening [33]. In the present study, after 6 or 24 h exposure to LPS, the comprehensive profiling suggested that protein-coding genes were frequently enriched in GO:007023 (post-chaperonin tubulin folding change).…”
Section: Lps Is Toxic To Cultured Eukaryotic Cells and Inhibites In Vitro Microtubulementioning
confidence: 47%